Role and Optimization of the Active Oxide Layer in TiO2‐Based RRAM. (15th December 2015) - Regoutz, Anna; Gupta, Isha; Serb, Alexantrou; Khiat, Ali; Borgatti, Francesco; Lee, Tien‐Lin; Schlueter, Christoph; Torelli, Piero; Gobaut, Benoit; Light, Mark; Carta, Daniela; Pearce, Stuart; et al.
Abstract : TiO2 is commonly used as the active switching layer in resistive random access memory. The electrical characteristics of these devices are directly related to the fundamental conditions inside the TiO2 layer and at the interfaces between it and the surrounding electrodes. However, it is complex to disentangle the effects of film "bulk" properties and interface phenomena. The present work uses hard X‐ray photoemission spectroscopy (HAXPES) at different excitation energies to distinguish between these regimes. Changes are found to affect the entire thin film, but the most dramatic effects are confined to an interface. These changes are connected to oxygen ions moving and redistributing within the film. Based on the HAXPES results, post‐deposition annealing of the TiO2 thin film was investigated as an optimisation pathway in order to reach an ideal compromise between device resistivity and lifetime. The structural and chemical changes upon annealing are investigated using X‐ray absorption spectroscopy and are further supported by a range of bulk and surface sensitive characterisation methods. In summary, it is shown that the management of oxygen content and interface quality is intrinsically important to device behavior and that careful annealing procedures are a powerful device optimisation technique. Abstract : TiO2 is one of the most widely used active switching layers in resistive random access memory . Spectroscopy is an excellent way to probe its surface, interface, and bulk properties in order to locate and identify physical and chemical changes upon biasing of a device. Oxygen content and interface quality can be optimised through careful annealing procedures resulting in improved device behavior.